(untitled) (Biological Sciences - PJSIR, 1999)
Free radical terpolymerizationof methylmethacrylate(MMA),n-butylacryalte(BA)and2-cthylhexyl acrylateusing methyl ethyl ketone as solvent was accomplished at 60 "C, It was observed that all the monomers participated in the reaction simultaneously andformedterpolymerin all monomericratios.The product,apartterpolymer alsocontained smallquantityofhomopolymersofthemonomersusedinthereaction.Terpolymersof 175000-590000wereobtained which werefoundtobe viscous,highlytacky,softatroomtemperatureandsolubleinmostoftheorganic solvents.The refractive indexofterpolyrner sampleswasfoundtobe 1.4945-1.4946.This terpolymermaybeused inthe modifica- tionofchlorinated rubberasthefilmformingagentonleather.